The effect of solar radiation on radio signal for radio astronomy purposes [Kesan radiasi solar terhadap isyarat radio untuk kajian astronomi radio] - Roslan, Umar; Nor Hazmin, Sabri; Atiq Wahidah, Azlan (Malaysian Society of Analytical Sciences, 2015)
Radio astronomy is a subfield of astronomy which is discovers the celestial objects at radio frequencies. Observation in radio astronomy is conducted using single antenna or array of antennas, known as radio telescope. Other than that, radio astronomy also holds an advantage over other alternatives to optical astronomy due to its capability of observing from the ground level. In this study, the effect of solar radiation that contributes the Radio Frequency Interferences (RFI) is reviewed. The low RFI level is required to set up the radio telescope for radio astronomy observation. The effect of solar radiation on radio signal was investigated by determining the RFI pattern using spectrum analyzer. The solar radiation data was obtained from weather station located at KUSZA Observatory, East Coast Environmental Research Institute (ESERI), UniSZA. We can conclude that the solar radiation factor give the minimum significant effect to radio signal.